Seleção de clones de batata de curta dormência, alta qualidade de processamento e adaptados aos cultivos de primavera e outono - Müller, Douglas Renato (2008)
Selection of potato clones might be done during spring and autumn grown seasons of Rio Grande do Sul (RS). These grown seasons have contrasting conditions of temperature, photoperiod and solar irradiation, which may affect tuber dormancy and chip processing quality. The objectives of this work were to identify potato clones with short dormancy, high chip quality and adaptation to spring and autumn grown conditions of RS. Tubers of 21 clones were produced during spring 2006 and autumn 2007. Tubers were left 15 days for healing, stored at 10ºC and 20ºC and evaluated. Dormancy evaluation was based upon percentage of sprouted tubers, number of sprouts per tuber, period (days) to 80% of sprouted tubers and fresh weight loss. Chip quality was evaluated as reduced sugars, dry mass, starch and amylase contents and chip color. All evaluations were done at 0, 30, 60 and 90 days of storage. Different group of clones were selected considering spring and autumn conditions, but SMA508-2, SMA508-4 and SMA519-1 had good performance in both seasons. Tubers produced during autumn season showed higher dormancy period and lower dry mass and starch contents than those of spring season. Storage temperature affected tuber quality and dormancy period. Tubers produced during autumn season and stored at 10oC had higher reduced sugars and lower amylase than those of spring season; however, tubers produced during spring season had lower dry matter and darker chips. The storage temperature of 10oC reduced the percentage of sprouted tubers and fresh weight losses of both grown seasons. Clonal selection depended upon storage temperature and the clone SMA519-1 had the best combination of chip quality traits in both season and storage temperature conditions. Tubers produced during spring season and stored at 10oC resulted in the highest selection gain for processing quality, but selection gain for short dormancy was maximized when tubers were produced during autumn season.